The Concept of Qualification Assessment - V. I. Blinov; O. F. Batrova; Y. Y. Yesenina; A. A. Faktorovitch (Russian State Vocational Pedagogical University, 2015)
The necessity of changing the approach to qualification assessment appears to be one of the main topics for discussion in the modern scientific pedagogic society. In the sphere of vocational education both in Russia and abroad, the emphasis is increasingly shifting to the learning outcomes: the expediency principle is regarded as the leading one; the operational component of professional readiness takes the first place; the results of mastering the educational program, as well as self-education and self- development, are viewed as providing the qualification significant for the labor market and based on the actual work requirements.Unfortunately, there is no unified methodology of qualification assessment; such integrated assessment of professional readiness for applying the acquired knowledge and skills in practice is urgently needed. The authors recommend a new concept of qualification assessment based on the experience of higher vocational educational establishments both in Russia and abroad. The reasons for changing the content of qualification concept are out- lined, the principles of quality assessment in modern conditions are revealed along with the concept terminology mechanism and method of independent expertise procedure.